While systolic cardiomyocyte function is preserved, diastolic myocyte function and recovery from acidosis are impaired in CaMKIIδ-KO mice - Neef, Stefan; Sag, Can M.; Daut, Maria; Bäumer, Henrik; Grefe, Clemens; El-Armouche, Ali; DeSantiago, Jaime; Pereira, Laetitia; Bers, Donald M.; Backs, Johannes; Maier, Lars S. (Journal of molecular and cellular cardiology, 2013)
Objective - CaMKII contributes to impaired contractility in heart failure by inducing SR Ca2+-leak. CaMKII-inhibition in the heart was suggested to be a novel therapeutic principle. Different CaMKII isoforms exist. Specifically targeting CaMKIIδ, the dominant isoform in the heart, could be of therapeutic potential without impairing other CaMKII isoforms. - Rationale - We investigated whether cardiomyocyte function is affected by isoform-specific knockout (KO) of CaMKIIδ under basal conditions and upon stress, i.e. upon ß-adrenergic stimulation and during acidosis. - Results - Systolic cardiac function was largely preserved in the KO in vivo (echocardiography) corresponding to unchanged Ca2+-transient amplitudes and isolated myocyte contractility in vitro. CaMKII activity was dramatically reduced while phosphatase-1 inhibitor-1 was significantly increased. Surprisingly, while diastolic Ca2+-elimination was slower in KO most likely due to decreased phospholamban Thr-17 phosphorylation, frequency-dependent acceleration of relaxation was still present. Despite decreased SR Ca2+-reuptake at lower frequencies, SR Ca2+-content was not diminished, which might be due to reduced diastolic SR Ca2+-loss in the KO as a consequence of lower RyR Ser-2815 phosphorylation. Challenging KO myocytes with isoproterenol showed intact inotropic and lusitropic responses. During acidosis, SR Ca2+-reuptake and SR Ca2+-loading were significantly impaired in KO, resulting in an inability to maintain systolic Ca2+-transients during acidosis and impaired recovery. - Conclusions - Inhibition of CaMKIIδ appears to be safe under basal physiologic conditions. Specific conditions exist (e.g. during acidosis) under which CaMKII-inhibition might not be helpful or even detrimental. These conditions will have to be more clearly defined before CaMKII inhibition is used therapeutically.